2015
DOI: 10.1007/s00128-015-1479-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Distribution of Heavy Metals, Polybrominated Diphenyl Ethers and Perfluoroalkyl Substances in Surface Sediment from the Dayan River, South China

Abstract: In this study, surface sediment samples were collected from 11 sites in the Dayan River near an electronic waste site in Qingyuan. Heavy metals, polychlorinated biphenyls (PBDEs) and perfluoroalkyl substances (PFASs) were detected. The concentrations of Cu, Zn, Pb and Cd ranged from 12.1 to 641, 47.1 to 891, 39.2 to 641, 0.12 to 2.07 mg/kg dw, respectively. Total PBDEs ranged between 0.052 and 126.64 ng/g dw. BDE-47 and BDE-99 were the predominant PBDEs. The concentrations of PFASs in sediments ranged between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Elevated concentrations of PFOS have been reported in sediment from a river near an e-waste recycling site in South China (up to 3.72 ng/g dry weight) when compared with sediment from other water bodies in China. A strong positive correlation among Cu, Zn, PFOA, and PBDEs indicated that several contaminants were related to each other and originate from e-waste recycling activities . Furthermore, a recent study showed that soil from a fluoropolymer industry contained elevated concentrations of PFOA .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated concentrations of PFOS have been reported in sediment from a river near an e-waste recycling site in South China (up to 3.72 ng/g dry weight) when compared with sediment from other water bodies in China. A strong positive correlation among Cu, Zn, PFOA, and PBDEs indicated that several contaminants were related to each other and originate from e-waste recycling activities . Furthermore, a recent study showed that soil from a fluoropolymer industry contained elevated concentrations of PFOA .…”
Section: Results and Discussionmentioning
confidence: 99%
“…A strong positive correlation among Cu, Zn, PFOA, and PBDEs indicated that several contaminants were related to each other and originate from e-waste recycling activities. 45 Furthermore, a recent study showed that soil from a fluoropolymer industry contained elevated concentrations of PFOA. 46 Therefore, higher serum PFAS concentration in e-waste area residents than the reference population suggested that e-waste dismantling activities are a source of exposure to PFASs.…”
Section: Environmental Science and Technology Lettersmentioning
confidence: 99%
“…Further, they are added to various materials such as electronic equipment, plastics, carpet liners and textiles [2,3]. Cd and BDEs coexisted in dust surface [4], sediment from river [5] and even in organisms [6]. The coexistence of Cd and BDE in the environment and biological systems poses a substantial risk to human health, but their potential joint toxicities remain so far elusive [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PFCAs always coexist with various contaminants in real aquatic environments. Zheng, et al [19] investigated some sediment samples collected from the Dayan River and found that heavy metals co-occur with PFCAs and they share a common anthropogenic source. Although most of these compounds are present at low concentrations, many of them raise considerable toxicological concerns, particularly when present as components of complex mixtures, which may interact and pose associated effects on aquatic environments [20].…”
Section: Introductionmentioning
confidence: 99%